Mechanical analysis of overhead throwing in Cricket - Hussain, I.; Bari, M. A. (International Journal of Sports Science and Engineering, 2011)
This paper considers the kinematic characteristics of over arm throwing with particular emphasis on the techniques of throwing in cricket. The technique is subdivided into: (1) Wind up phase, (2) late cocking Phase (3) arm acceleration and (4) instant of ball release. The study was used to form the samples as, 10 elite cricket players. The ages of the players were (mean ± 23.50). The physical characteristics of height (Mean: 1169.4-172.4cm)), weight (57.8-61.3). Each over head maximal and sub maximal successful attempt for each throwing distances 20m and 10m with 1800,1120 and 450 approach angle at 900 target angle from the stump were recorded using Sony DV cameras in a field setting with (1/2000 shutter speed and at 30-60fps). The cameras were set-up on a rigid tripod and secured to the floor in the location. First camera was located to obtain maximum accuracy and second camera located to view the throwing performances, at given specified distance in the reconstruction of the two dimensional co-ordinate. The location of camera were chosen so that the optical axes of camera intersected perpendicularly to the designated plane .The accuracy of throwing performances were considered in identify the footage for addition and were subjected to analysis. Result revealed that the ball speed had to be high to carry the full distance of the throw in the shortest time. Using a lower angle of release can further reduce flight time, as for the 20-m throw, for which a much flatter projection was used.